Practical Stability of Impulsive Discrete Systems with Time Delays - Liangji Sun; Chengyan Liu; Xiaodi Li (Abstract and Applied Analysis)
The purpose of this paper is to investigate the practical stability problem for impulsive discrete systems with time delays. By using Lyapunov functions and the Razumikhin-type technique, some criteria which guarantee the practical stability and uniformly asymptotically practical stability of the addressed systems are provided. Finally, two examples are presented to illustrate the criteria.